Education for Student with Cerebral palsy on Reducing Drooling through Oral Motor Exercise - Damri, Damri; Nurhastuti, Nurhastuti; Putri, Sintia; Putri, Sentia Andani; Jatiningsiwi, Tata Gading; Iliško, Dzintra (Jurnal Ilmu Pendidikan, 2024)
This study aims to reduce drooling through oral motor exercises for cerebral palsy students in Special School in Padang, Indonesia. This study used quantitative research methods with a Single Subject Research (SSR) approach with A-B-A design from February to September 2021. The research data was collected by observing one child with cerebral palsy, recording events, and assessing oral motor exercise. All data was analyzed descriptively using visual graph analysis tools. Overall, the results showed that oral motor exercise effectively reduced drooling in cerebral palsy students. This was evidenced by the mean level obtained in the baseline-1 (A1) condition, which was 14.66; in the intervention condition (B), it decreased to 8.15; and in the baseline-2 (A2) condition, it again reduced to 3. Then, the results of data analysis in the conditions and between conditions also showed a tendency toward stability, an estimated directional tendency, and data trace and level changes that decreased positively. The percentage of overlap in the baseline-1 (A1) condition is 0%, while the percentage of overlap in the baseline-2 (A2) condition is 15 percent so the hypothesis can be accepted. These findings imply that the selection of oral motor exercises effectively reduces drooling in students with cerebral palsy